2013
DOI: 10.1038/nature12178
|View full text |Cite
|
Sign up to set email alerts
|

Polymerase IV occupancy at RNA-directed DNA methylation sites requires SHH1

Abstract: DNA methylation is an epigenetic modification that plays critical roles in gene silencing, development, and genome integrity. In Arabidopsis, DNA methylation is established by DOMAINS REARRANGED METHYLTRANSFERASE 2 (DRM2) and targeted by 24 nt small interfering RNAs (siRNAs) through a pathway termed RNA-directed DNA methylation (RdDM)1. This pathway requires two plant-specific RNA polymerases: Pol-IV, which functions to initiate siRNA biogenesis and Pol-V, which functions to generate scaffold transcripts that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
427
3
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 346 publications
(447 citation statements)
references
References 37 publications
16
427
3
1
Order By: Relevance
“…Since the Pol IV-interacting protein DTF1/SHH1 binds to H3K9me2 and helps recruit Pol IV to a subset of RdDM loci [21,22], we tested the possibility that DTF1/ SHH1 preferentially targets ID and/or PD loci. However, we found that the ID loci are less enriched for DTF1-dependent DMRs (Supplementary information, Figure S5), suggesting that multiple factors are involved in recruiting Pol IV to different types of RdDM target loci.…”
Section: Dicer-independent Dna Methylation At Rddm Target Locimentioning
confidence: 99%
See 1 more Smart Citation
“…Since the Pol IV-interacting protein DTF1/SHH1 binds to H3K9me2 and helps recruit Pol IV to a subset of RdDM loci [21,22], we tested the possibility that DTF1/ SHH1 preferentially targets ID and/or PD loci. However, we found that the ID loci are less enriched for DTF1-dependent DMRs (Supplementary information, Figure S5), suggesting that multiple factors are involved in recruiting Pol IV to different types of RdDM target loci.…”
Section: Dicer-independent Dna Methylation At Rddm Target Locimentioning
confidence: 99%
“…It has been shown that an H3K9me2-binding protein, DTF1/SHH1, is required for Pol IV recruitment to a subset of RdDM target loci [21,22], whereas two SRA-domain-containing proteins SUVH2/9, which bind to methylated DNA, are required for Pol V occupancy at RdDM loci [23,24]. Both DTF1/ SHH1 and SUVH2/9 interact with putative ATP-dependent chromatin remodeling factors, including CLSY1 and DRD1, which are presumed to facilitate transcription by RNA Pol IV and Pol V, respectively [22,24].…”
Section: Introductionmentioning
confidence: 99%
“…Double-stranded siRNAs are amplified through RNA-DEPENDENT RNA POLYMERASE2 and cleaved by the endoribonuclease DICER-LIKE3. These siRNAs are then loaded onto ARGONAUTE4 (AGO4), and AGO4-associated siRNAs are predicted to guide the de novo methyltransferase activity of DOMAINS REARRANGED METHYLASE2 (Zilberman et al, 2004;Gao et al, 2010), leading to RdDM (Haag and Pikaard, 2011;Law et al, 2013). The maintenance of DNA methylation requires METHYLTRANSFERASE1 (MET1), which encodes a DNA methyltransferase, as well as DECREASE IN DNA METHYLATION1 (DDM1), which is a SWI/SNF2-like chromatin-remodeling protein (Jeddeloh et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The work has identified principles underlying how methylation in plants is controlled by a specific histone methylation mark through a self-reinforcing loop between a DNA-specific methyltransferase enzyme and a histonespecific lysine methyltransferase (18). The two are also identifying and characterizing the structure of proteins that mediate the RNA-directed DNA methylation pathway in plants (19). Patel says that his "contributions to epigenetic regulation, which recently have been expanded to histone chaperones" (20) provide fundamental insights, similar to his contributions to the RNA interference field.…”
Section: Codes To Live Bymentioning
confidence: 99%
“…"Because India was a developing country, science was what we learned in textbooks, with minimal practical experience," Patel explains. Drawn to the United States, at the age of 19 Patel enrolled in graduate school at the California Institute of Technology (Caltech). In the laboratory of Jack Roberts, Patel got his first experience working with NMR spectroscopy, a tool to visualize molecular structure that would figure prominently in his early career.…”
Section: America Beckonsmentioning
confidence: 99%